2007
DOI: 10.1021/jp075368y
|View full text |Cite
|
Sign up to set email alerts
|

Size- and Orientation-Dependent Photovoltaic Properties of ZnO Nanorods

Abstract: ZnO nanorod arrays on an ITO substrate and nanorod powder have been prepared via a chemical method in aqueous solution at low temperature. Two dimensions of composite nanorods in the arrays were obtained by controlling the reaction time. SEM, XRD, UV-vis transmission, and PL measurements have been utilized to characterize the samples. The surface photovoltage (SPV) spectra of the three samples have been comparatively investigated by a lock-in amplifier with dc bias and Kelvin probe (KP) based measurements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 52 publications
3
80
0
Order By: Relevance
“…In these systems, SPV has been shown to saturate on time scales ranging between only picoseconds to microseconds [57,60], so the long-time scale effects seen for these TI surfaces can also involve photonstimulated desorption. Having said that, we do note that SPV time scales of a few minutes, comparable to the τ 1 's found in this study, have been reported for the SPV onset in ZnO nanorods [61].…”
Section: B Physical Phenomena Induced By High-flux Illuminationsupporting
confidence: 88%
“…In these systems, SPV has been shown to saturate on time scales ranging between only picoseconds to microseconds [57,60], so the long-time scale effects seen for these TI surfaces can also involve photonstimulated desorption. Having said that, we do note that SPV time scales of a few minutes, comparable to the τ 1 's found in this study, have been reported for the SPV onset in ZnO nanorods [61].…”
Section: B Physical Phenomena Induced By High-flux Illuminationsupporting
confidence: 88%
“…59(b). The small open circuit voltage was attributed to the dominance of differently exposed crystal facets of the nanowires [478], as also evidenced by surface photovoltage studies [479]. The energy conversion efficiency [478].…”
Section: Inorganic P-n Junction Solar Cellsmentioning
confidence: 77%
“…For the SPC mode, a comblike ITO electrode with an external bias (10.0 V) on two sides was used, [35] while for the SPV mode, a sandwich-like structure in which the samples were directly sandwiched between two blank ITO electrodes was employed. [32,33] The details of TPV system have been described previously. [38,40] As for the measurement, the sample chamber consisted of an ITO electrode, a 10 mm thick mica spacer as electron isolator (to prevent the photoinduced electrons in the semiconductor from being directly injected to the electrode), and a platinum wire gauze electrode (with a transparency of about 50 %).…”
Section: Methodsmentioning
confidence: 99%